Weekend admissions and mortality for major acute disorders across England and Wales: record linkage cohort studies - Stephen E. Roberts; Ann John; Keir E. Lewis; Jonathan Brown; Ronan A. Lyons; John G. Williams (BMC Health Services Research, 2019)
Abstract Background To establish which major disorders are susceptible to increased mortality following acute admissions on weekends, compared with week days, and how this may be explained. Methods Cohorts based on national administrative inpatient and mortality data for 14,168,443 hospitalised patients in England and 913,068 in Wales who were admitted for 66 disorders that were associated with at least 200 deaths within 30 days of acute admission. The main outcome measure was the weekend mortality effect (defined as the conventional mortality odds ratio for admissions on weekends compared with week days). Results There were large, statistically significant weekend mortality effects (> 20%) in England for 22 of the 66 conditions and in both countries for 14. These 14 were 4 of 13 cancers (oesophageal, colorectal, lung and lymphomas); 4 of 13 circulatory disorders (angina, abdominal aortic aneurysm, peripheral vascular disease and arterial embolism & thrombosis); one of 8 respiratory disorders (pleural effusion); 2 of 12 gastrointestinal disorders (alcoholic and other liver disease); 2 of 3 ageing-related disorders (Alzheimer’s disease and dementia); none of 7 trauma conditions; and one of 10 other disorders (acute renal failure). Across the disorders, 64% of the variation in weekend mortality effects in England and Wales was explained by reductions in admission rates at weekends and the medical disease category. Conclusions The effect of weekend admission on 30 day mortality is seen mainly for cancers, some circulatory disorders, liver disease and a few other conditions which are mainly ageing- or cancer-related. Most of the increased mortality is associated with reduced admission rates at weekends and the medical disease category.